Trade liberalization and national food security: rice trade between Bangladesh and India - Dorosh, Paul A. (Elsevier, 2001)
Following a poor harvest in late 1997 and a massive flood in 1998, private sector traders in Bangladesh imported several million metric tons of rice from India. This paper presents evidence that this trade, made possible by separate trade liberalizations in India and Bangladesh in the early 1990s, augmented domestic supplies and stabilized prices in Bangladesh at import parity levels... The positive contribution of trade liberalization to short-run food security in Bangladesh in recent years does not minimize the importance of increased agricultural productivity and rural economic growth to provide rural poor households with sufficient incomes to acquire food. Nonetheless, the Bangladesh experience shows that trade liberalization offers potential benefits for national food security by enabling a rapid increase of food supplies following domestic production shortfalls.